Prevention Behavior Of Diabetic Ulcuses In Patients With Diabetes Mellitus In The Working Area Of Puskesmas Kota Binjai - Wirda Faswita; Johani Dewita Nasution; Eqlima Elfira (Universitas Haji Sumatera Utara, 2023)
Diabetes Mellitus (DM) is a very dangerous disease, because it can cause many complications. One of the complications that often occurs in DM sufferers is the occurrence of Diabetic Ulcers. In the work area of ​​the Binjai City Health Center in 2021, data on visits for DM sufferers were recorded, namely 1,662 people. Diabetic ulcers can be prevented if the risk level is detected early. this is to find out how the behavior of Diabetes mellitus in the prevention of diabetic ulcers in the Binjai City Public Health Center area. This research is a type of quantitative research with a descriptive study design. The sample in this study were 23 DM sufferers in the Binjai City Health Center area, using a total sampling technique. The results showed that most DM sufferers in the Binjai Kota Health Center area were at a moderate level, while some others were at low and high risk for the occurrence of Diabetic Ulcers. These results are known that the majority of respondents based on negative behavior of 21 respondents (91.3%) and positive behavior of 2 respondents (50%). Efforts must be made to avoid the occurrence of Diabetic Ulcers such as health education about foot care which also needs to be increased, so that the prevention of Diabetic Ulcers is more optimal